Needs of drainage for sustainable crop production in the saline environment - Datta, K. K., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
Sustainability of irrigated agriculture in the arid and semi-arid regions of the country has faced the challenge of alkalinity/salinity problems associated with soils and irrigation waters. One of the major problems confronting present day agriculture is decreasing availability of good quality irrigation water. With increasing demand and decreasing availability of good quality waters, there is growing tendency among the farmers to use these poor quality waters for crop production. Indiscriminate use of poor quality waters in the absence of proper soil-water-crop management practices poses grave risks to soil health and environment. In India about 36 percent of irrigated lands have been damaged at different levels due to such practices. This disappointing picture due to faulty irrigation development. Failure to create "enabling condition", lack of institutional support, lack of provision of drainage, all contributed to failure to prevent the growing problem of water logging and salinity. Area under canal irrigation during the last three decades was only 19 percent but area increase through tubewells has been of the order of 160 and 189 percent in Haryana and Punjab, respectively. The scenario on ground water utilisation is not the same in several other states or their specific areas disadvantaged either with poor quality aquifer yields or their quality. Surveys rate 32-84 per cent of the presently operable wells of different states to be of poor quality. A number of technological options are available (like improve water management practices through sprinkler, drip irrigation etc. (ii) conjunctive use of ground water where quality is poor, (iii) skimming well/doruvu technology where shallow ground water management is needed and (iv) subsurface drainage (SSD) where water table is high and quality of ground water is poor) to augment the effective supply of land. Though these options are crucial, they have themselves tended to be centralized and technocratic and hence capital intensive. For such reason, each of these prescribed strategies/remedies enjoyed the status of a 'privileged solution' at one time or other. There was no effort to harness the synergic benefits of those options, with the result that no progress was achieved in testing these strategies together. It does not stimulate testing and modification and does not promote a 'learning process' strategy. This paper mainly suggests different policy options and strategic approaches like institutional intervention through participatory approaches from technical mode to participatory mode, group incentives, price policy for different water saving devices and clear cut ownership right for sustaining crop production in saline environments of India.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.